2023
DOI: 10.1186/s12916-023-02844-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses identified novel susceptibility loci for pulmonary embolism among Han Chinese population

Abstract: Background A large proportion of pulmonary embolism (PE) heritability remains unexplained, particularly among the East Asian (EAS) population. Our study aims to expand the genetic architecture of PE and reveal more genetic determinants in Han Chinese. Methods We conducted the first genome-wide association study (GWAS) of PE in Han Chinese, then performed the GWAS meta-analysis based on the discovery and replication stages. To validate the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Currently, there are insufficient data to verify the association of mutations in the PLAT gene with venous or arterial thrombosis. 38 , 39 According to the prediction, the mutation c.1411T>C (p.Y471H) in PLAT is predicted to be probably harmful ( http://genetics.bwh.harvard.edu/pph2/ ), which is consistent with our clinical findings and research results. However, it has also been reported that the heterozygous point mutation c.1411T>C in PLAT is likely to be a non‐pathogenic benign mutation ( http://www.gnomad‐sg.org/ ), which may be the reason why the parents and daughter of the proband did not have venous thromboembolism events despite carrying heterozygous point mutation c.1411T>C in PLAT .…”
Section: Discussionsupporting
confidence: 89%
“…Currently, there are insufficient data to verify the association of mutations in the PLAT gene with venous or arterial thrombosis. 38 , 39 According to the prediction, the mutation c.1411T>C (p.Y471H) in PLAT is predicted to be probably harmful ( http://genetics.bwh.harvard.edu/pph2/ ), which is consistent with our clinical findings and research results. However, it has also been reported that the heterozygous point mutation c.1411T>C in PLAT is likely to be a non‐pathogenic benign mutation ( http://www.gnomad‐sg.org/ ), which may be the reason why the parents and daughter of the proband did not have venous thromboembolism events despite carrying heterozygous point mutation c.1411T>C in PLAT .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the coagulation function might be another mechanism that should be noted. One GWAS study has reported that LDL and TC were associated with an increased risk of pulmonary embolism, suggesting the lipids traits were involved in coagulation pathways [ 59 ]. Another MR study has demonstrated the causal associations between ADAMTS13/vWF and the risk of endometriosis, suggesting the involvement of coagulation factors in endometriosis development [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 We would like to address the specific points raised by Lixian Ji and Peng Shu as follows: Regarding the PE and VTE distinction : We acknowledge this oversight in our study and agree that it is crucial to specify that our study primarily focused on pulmonary embolism (PE) or PE with deep vein thrombosis (DVT). 3 , 4 By providing this clarification, we can prevent potential misconceptions and ensure that the implications of our findings are appropriately understood within the relevant context. On the instrumental variable clumping process : It should be noted that similar to GWAS studies, there is currently no standardized criterion for determining the appropriate clumping thresholds in Mendelian randomization (MR) research.…”
mentioning
confidence: 99%
“…Regarding the PE and VTE distinction : We acknowledge this oversight in our study and agree that it is crucial to specify that our study primarily focused on pulmonary embolism (PE) or PE with deep vein thrombosis (DVT). 3 , 4 By providing this clarification, we can prevent potential misconceptions and ensure that the implications of our findings are appropriately understood within the relevant context.…”
mentioning
confidence: 99%